(untitled) (Szociológiai Szemle, 2024)
Corruption is the gravest social and economic problem in the post-communist countries. In this study we analyse and compare the results of public opinion polls which were completed partly on a representative survey of the whole Hungarian population, and partly on a sample of leaders of public institutions. We tried to find answers to the following questions: What does corruption mean to the population? How often do they m eet with it in their private lives and official practice? What do they think about the extent of corruption in Hungary if compared to other countries and other historical periods? What do they think about the root and reasons of corruption? What is their opinion about the transparency of public institutions and political parties? The study gives a comparison of the opinion of the general population and of the representative leaders of elite professions.